2013
DOI: 10.1371/journal.pgen.1003178
|View full text |Cite
|
Sign up to set email alerts
|

MTERF3 Regulates Mitochondrial Ribosome Biogenesis in Invertebrates and Mammals

Abstract: Regulation of mitochondrial DNA (mtDNA) expression is critical for the control of oxidative phosphorylation in response to physiological demand, and this regulation is often impaired in disease and aging. We have previously shown that mitochondrial transcription termination factor 3 (MTERF3) is a key regulator that represses mtDNA transcription in the mouse, but its molecular mode of action has remained elusive. Based on the hypothesis that key regulatory mechanisms for mtDNA expression are conserved in metazo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
87
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(95 citation statements)
references
References 46 publications
8
87
0
Order By: Relevance
“…Several studies indicate a close relationship between the rDNA arrays, ribosomal biogenesis and the mitochondria [10][11][12][13] . For instance, recent evidence points to the import of 5S rRNAs into the mitochondria through a highly regulated process 35,36 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies indicate a close relationship between the rDNA arrays, ribosomal biogenesis and the mitochondria [10][11][12][13] . For instance, recent evidence points to the import of 5S rRNAs into the mitochondria through a highly regulated process 35,36 .…”
Section: Resultsmentioning
confidence: 99%
“…NATURE COMMUNICATIONS | DOI: 10.1038/ncomms5850 ARTICLE This protein regulates mitochondrial transcription and mitochondrial ribosome biogenesis 12 . These results suggest tight regulatory relationship between rDNA dosage, GE of ribosomal proteins and mtDNA abundance, which emerge in the context of naturally occurring variability among individuals (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…First, Surovtseva and Shadel (53) reported that mtRNA polymerase has a transcription-independent role in ribosome assembly, dependent to some degree on the interaction of mtRNA polymerase with the methyltransferase TFB1M. Second, Larsson's group (54) has shown that MTERF3 is both a negative regulator of mitochondrial transcription and a factor involved in mitochondrial ribosome assembly (55). MTERF3 and mtRNA polymerase were both identified as interacting with RNMTL1, possibly mediated by RNA structures (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Knockout Mterf3 mice are embryo lethal (Park et al, 2007). In the conditional Mterf3 heart knockout, levels of the 39S mitochondrial ribosomal subunit are reduced and ribosomal assembly is perturbed (Wredenberg et al, 2013); thereby, a novel role for mouse mTERF3 in the biogenesis of metazoan mitochondrial ribosomes was identified. Like Mterf3 knockout mice (Park et al, 2007), Mterf4 knockout mice are embryo lethal (Cámara et al, 2011).…”
mentioning
confidence: 99%